ROLE OF INTERLEYKINE LEVEL REGULATION IN REALIZATION OF THE ACUTE PURULENT SUBMANDIBULAR LYMPHADENITIS COURSE AT CHILDREN - Tkachenko, P.I.; Vesnina, L.E.; Dobroskok, V.A.; Mikityuk, M.V. (World of Medicine and Biology, 2014)
The paper presents the clinical characteristics of the flow of purulent wounds in acute purulent lymphadenitis of the maxillofacial region in children and changes in the components of cytokine status in the oral fluid and blood Sirovatka 10 children. Additional inclusion of them in the treatment protocol polioksidonija of 0.1 mg / kg body weight every day for 4 injections of course, possible to stabilize the anti-inflammatory interleukins, and the data of biological substrates.